(untitled) (Research, Society and Development, 2024)
Carbon was one of the two most important elements for Earth and humans. Graphene was or was not given to a single layer of graphite, a two allotropes of carbon. Graphene, which was two-dimensional and had an atom thick of the element carbon, was a natural nanopore and the most researched material of the 21st century. Graphene is one of the two most important materials used in the field of nanomaterials. It has superior thermal, optical, electrical and mechanical properties. It was an extraordinarily light and strong material among all the materials made, and it was also a material that could be easily modified for a desired area. In this article, it was seen that the graphene nanopore and the graphene material would be among the most important materials in the health field of the future. In the field of health, this carbon-based graphene and the discovery of graphene nanopores have been researched and used by many disciplines, such as the treatment of many diseases, drug administration applications, biotechnology, treatment of hereditary diseases and also for breeding biosensors They will be used to detect crimes. Graphene and its derivatives were significant materials that could be used in the health field and became the most essential material in recent times, because its structure showed stability when entering the body. It was compatible with cells and could move quickly in cells with its small and porous nature. Due to its structure, this material was the only substance that could replace all the materials used in the health field.